Whole-Exome Sequencing Revealed Mutations of MED12 and EFNB1 in Fetal Agenesis of the Corpus Callosum - Jiang, Ying; Qian, Ye-Qing; Yang, Meng-Meng; Zhan, Qi-Tao; Chen, Yuan; Xi, Fang-Fang; Sagnelli, Matthew; Dong, Min-Yue; Zhao, Bai-Hui; Luo, Qiong (Frontiers in Genetics, 2019)
Agenesis of the corpus callosum (ACC) is a birth defect in which the corpus callosum is either partially or completely missing. With recent advances in prenatal ultrasound, detection of ACC in obstetric practices is becoming more common. Etiologies of ACC include chromosome errors, genetic factors, prenatal infections, and other factors related to the prenatal environment. In an effort to elucidate more about the genetic influence in the pathogenesis of ACC, we identified, through whole-exome sequencing (WES), two gene mutations in two families with complete agenesis of the corpus callosum. These two mutations are located on chromosome X: one is a hemizygous missense mutation c.3746T>C (p. L1249P) in the gene mediator complex subunit 12 (MED12); the other one is a heterozygous missense mutation c.128+5G>C in gene ephrin B1 (EFNB1). Historically, early diagnosis of complete ACC during pregnancy has been difficult; however, WES has provided us with a creative avenue of diagnosis, combining identification of genetic mutations with prenatal imaging.